Heterotopic Ossification of the Inferior Vena Cava Wall: A Case Report and Literature Review - Tian, Jihua; Zhang, Li; Hu, Min; Zeng, Xing; Wang, Yongjun; Yang, Chunguang; Hu, Zhiquan (Frontiers in Surgery, 2021)
Masses of the inferior vena cava (IVC) are very diverse, most of which are thrombi and tumor thrombi, whereas heterotopic ossification of IVC has never been reported. Heterotopic ossification (HO) is the formation of mature lamellar bone outside normal bones and in soft tissues. Some researchers believe that HO is a manifestation of vascular calcification. Here we present a case of HO of the inferior vena cava (IVC) wall. A 68-year-old female patient diagnosed with a retroperitoneal mass was found to have a primary mass of the inferior vena cava wall during surgery. Histopathological examination after surgical resection revealed that the mass was mainly composed of mature bone tissues and hematopoietic tissues of bone marrow, there was still no recurrence and the patient was symptom-free 15-months after the surgery. HO of the inferior vena cava wall is very rare, with large volume it can affect the circulation, and this case remind us that it can be cured by surgical resection.